Aplikasi Augmented Reality Pada Photo Booth di Kagungan Dalem Wahanarata Karaton Ngayogyakarta Hadiningrat - Ambar Setyawan; Norhikmah (Jurnal ICT: Information Communication & Technology, 2024)
Kagungan Dalem Wahanarata Karaton Ngayogyakarta Hadiningrat, formerly known as Museum Kereta Keraton, houses a collection of fascinating historical objects such as royal carriages, palanquins, and jempana. Despite its high potential for educational tourism, the number of visitors remains low. This research aims to develop an augmented reality (AR) photo booth application as a solution to improve the visitor experience at museums. The AR photo booth application is designed to allow visitors to interact virtually with the museum's collections. Visitors can take pictures with 3D avatars of grooms (pekatik) and horses, and learn historical and cultural information through AR technology. This research employs the waterfall software development life cycle (SDLC) methodology, which consists of five stages: user needs analysis, design, implementation, application testing, and delivery & maintenance. It is hoped that this AR photo booth application can increase the museum's attractiveness, make the visitor experience more interactive and educational, and ultimately, increase interest in returning to the museum.